2003
DOI: 10.1007/s00125-003-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

P38 mitogen-activated protein kinase mediates hexosamine-induced TGFβ1 mRNA expression in human mesangial cells

Abstract: Aims/hypothesis. The hexosamine pathway has been implicated in the induction of TGFβ1 expression and in the pathophysiology of diabetic glomerulopathy. Glucose-induced TGFβ1 expression is mediated by p38 mitogen-activated-protein-kinase (p38-MAPK) and this kinase is activated in the diabetic glomeruli. We examined whether the p38-MAPK is implicated in hexosamine-induced TGFβ1 mRNA expression in human mesangial cells. Methods. The products of the hexosamine biosynthetic pathway were increased by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Renal p38 in experimental diabetes R Komers et al lation of products of glycation reactions, and oxidative stress, have been shown to induce p38 signaling in mesangial cells, podocytes and in proximal tubular cells in vitro. 3,16,[23][24][25] In agreement with these findings, present studies, conducted in more clinically relevant settings, show that poor metabolic control is the major determinant of p38 activity in the diabetic kidney. Our findings are also in agreement with limited in vivo evidence in the setting of Type 1 diabetes, suggesting increased expression of P-p38 protein expression in wholekidney homogenates harvested from mice early after induction of STZ-diabetes.…”
Section: Renal P38 In Experimental Diabetessupporting
confidence: 90%
See 2 more Smart Citations
“…Renal p38 in experimental diabetes R Komers et al lation of products of glycation reactions, and oxidative stress, have been shown to induce p38 signaling in mesangial cells, podocytes and in proximal tubular cells in vitro. 3,16,[23][24][25] In agreement with these findings, present studies, conducted in more clinically relevant settings, show that poor metabolic control is the major determinant of p38 activity in the diabetic kidney. Our findings are also in agreement with limited in vivo evidence in the setting of Type 1 diabetes, suggesting increased expression of P-p38 protein expression in wholekidney homogenates harvested from mice early after induction of STZ-diabetes.…”
Section: Renal P38 In Experimental Diabetessupporting
confidence: 90%
“…1 In the kidney, such aberrant activation of MAPK cascades may perturb the balance of humoral and cytokine systems responsible for regulating vascular tone, permeability, renal cellular growth, and composition of the extracellular/mesangial matrix (ie, factors associated with the development of diabetic nephropathy). 2,3 p38 mitogen-activated protein kinase (p38), a member of the MAPK family, is activated by a number of stimuli. As a stress-activated kinase, p38 is activated by physical and chemical stress factors, inflammatory cytokines, and vasoactive and growth factors, resulting in growth promotion, apoptosis, oxidative stress, and vasoconstriction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, all performed under different cellular contexts, have recently demonstrated that increases in HBP flux can lead to increased MAPK activation (16,78,(83)(84)(85). In addition, HBP-driven changes in p44/p42 activation have been suggested to occur through a Rho GTPase-mediated mechanism in cultured rat aortic smooth muscle cells (78).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated rat and human islets, HepG2 human liver carcinoma cells, MIN6 beta cells, and small pieces of mouse heart were lysed in 200 μl ice-cold lysis buffer (100 mmol/l TrisHCl, pH 8.0, 500 mmol/l LiCl, 10 mmol/l EDTA, 0.1% [w/v] lithium dodecylsulphate, 5 mmol/l dithiothreitol) and mRNAs were isolated using a Dynabeads oligo (dT) 25 kit (Dynal, Oslo, Norway) according to the manufacturer's instructions. cDNAs were synthesised from each mRNA sample immediately, using Superscript II reverse transcriptase (200 U), oligo(dT) 18 (1 μg) and random 10-mers (1 μg) as previously described [23], and cDNAs were diluted tenfold in tRNA (10 μg/ml) and stored at −85°C.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%